Emergence, Power Relations, and Proponents: A New Display of War and Nazi Crimes at the House of History at the Museum Niederösterreich - Rapp, Christian; Thuile, Andrea; Vogl, Benedikt (Österreichische Zeitschrift für Geschichtswissenschaften, 2023)
The House of History (Haus der Geschichte im Museum Niederösterreich) opened in September 2017 as a new part of the Museum Niederösterreich in St. Pölten. 2021 saw a major redesign of exhibition parts addressing European history between 1914 and 1945 and its close connection to historical events on a local and regional level at the same period of time. The aim was to refocus the exhibition’s content and achieve further evolution of its display and mediation concept. The new presentation takes a longer perspective on social and political developments and highlights continuities and processes. Nazi atrocities are shown in their historical context and conveyed through individual victim biographies. Violent images are employed consciously and in a manner that encourages viewer empathy without precluding their ability to reflect rationally on the subject. The guiding considerations of our revision will be sketched in this article.